IGFBP3 Modulates Lung Tumorigenesis and Cell Growth through IGF1 Signaling - Yong Antican Wang; Yunguang Sun; Joshua D. Palmer; Charalambos Solomides; Li‐Ching Huang; Yu Shyr; Adam P. Dicker; Bo Lü (2017)
Insulin-like growth factor binding protein 3 (IGFBP3) modulates cell growth through IGF-dependent and -independent mechanisms. Reports suggest that the serum levels of IGFBP3 are associated with various cancers and that IGFBP3 expression is significantly decreased in cisplatin (CDDP)-resistant lung cancer cells. Based on these findings, we investigated whether Igfbp3 deficiency accelerates mouse lung tumorigenesis and if expression of IGFBP3 enhances CDDP response by focusing on the IGF1 signaling cascade. To this end, an Igfbp3-null mouse model was generated in combination with KrasG12D to compare the tumor burden. Then, IGF-dependent signaling was assessed after expressing wild-type or a mutant IGFBP3 without IGF binding capacity in non-small cell lung cancer (NSCLC) cells. Finally, the treatment response to CDDP chemotherapy was evaluated under conditions of IGFBP3 overexpression. Igfbp3-null mice had increased lung tumor burden (>2-fold) and only half of human lung cancer cells survived after expression of IGFBP3, which corresponded to increased cleaved caspase-3 (10-fold), inactivation of IGF1 and MAPK signaling. In addition, overexpression of IGFBP3 increased susceptibility to CDDP treatment in lung cancer cells. These results, for the first time, demonstrate that IGFBP3 mediates lung cancer progression in a KrasG12D mouse model. Furthermore, overexpression of IGFBP3 induced apoptosis and enhanced cisplatin response in vitro and confirmed that the suppression is in part by blocking IGF1 signaling.Implications: These findings reveal that IGFBP3 is effective in lung cancer cells with high IGF1 signaling activity and imply that relevant biomarkers are essential in selecting lung cancer patients for IGF1-targeted therapy. Mol Cancer Res; 15(7); 896-904. ©2017 AACR.